1999
DOI: 10.1002/(sici)1097-4628(19991107)74:6<1490::aid-app22>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fillers and plasticizers on the performance of novel heat and oil-resistant thermoplastic elastomers from nylon-6 and acrylate rubber blends

Abstract: ABSTRACT:The effects of various fillers (SRF black, silica, and clay) and plasticizers (dibutyl phthalate and dioctyl phthalate) on the mechanical, dynamic mechanical, and rheological properties and on the heat and oil resistance of the thermoplastic elastomeric reactive blends of nylon-6 and acrylate rubber (ACM) were investigated. The mixing torque behavior of the blends in Brabender Plasticorder shows reduced extent of interaction between the two component polymers in the presence of both fillers and plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 12 publications
(11 reference statements)
0
34
0
Order By: Relevance
“…Figure 6 compares the SEM micrographs of PP/ACM (50:50 parts) blends as a function of the compatibilization and vulcanization. The white region corresponds to the rubber phase, which was selectively stained by RuO 4 . Non vulcanized and non compatibilized blend presented a co-continuous structure, with large rubber phase because of the incompatibility between the phases.…”
Section: Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 6 compares the SEM micrographs of PP/ACM (50:50 parts) blends as a function of the compatibilization and vulcanization. The white region corresponds to the rubber phase, which was selectively stained by RuO 4 . Non vulcanized and non compatibilized blend presented a co-continuous structure, with large rubber phase because of the incompatibility between the phases.…”
Section: Morphologymentioning
confidence: 99%
“…Consequently a fine morphology is usually achieved for these blends, which contributes to an improvement of the overall properties. Some few examples of ACM -based elastomer thermoplastics are reported in the literature and include blends with nylon [4][5][6][7], poly(vinyl chloride) (PVC) [8,9], poly(vinylidene fluoride) (PVDF) [10], poly (ethylene terephthalate) [11] and chlorinated polypropylene [12]. In all these blends, the thermoplastic component is polar, and presents some affinity with the ACM rubber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best way to achieve commercially viable products with outstanding properties is through the addition of filler and/or blending with other thermoplastic or rubber. Several researchers have reported the use of ACM rubbers in blends with some thermoplastic as nylon [2][3][4][5] , poly (vinyl chloride) [6][7] , ethylene -vinyl acetate (EVA) copolymers [8] , poly(vinylidene fluoride) (PVDF) [9] , poly (ethylene terephthalate) [10] , chlorinated polypropylene [11] and polypropylene [12] , as well as with few rubbers as fluorocarbon rubber [13][14][15][16][17] and natural rubber [18][19][20] . Recently we have reported some results involving mechanical and dynamic mechanical properties of ACM/NBR blends aiming to develop a system with better heat and oil resistance than pure NBR elastomer and better mechanical performance than ACM [21] .…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the existence of a high interfacial tension between the two polymers. Bhowmick et al [16][17][18][19][20][21][22][23][24] also reported various TPEs and TPVs. Recently Naskar et al [25][26][27][28][29][30] extensively studied the effect of various peroxides including multifunctional peroxides as crosslinking agents in PP/EPDM TPVs.…”
Section: Introductionmentioning
confidence: 99%